Acupressure Technique to Reduce Dysmenorrhea - Yani Purwaningsih; Arfiana Arfiana; Ribkha Itha Idhayanti (Midwifery and Nursing Research, 2020)
Background: Dysmenorrhea or menstrual pain was one of the most common complaints in young women who come to the clinic or doctor. As many as 90% of Indonesian women had experienced menstrual pain. Non-pharmacological therapy that can be used to reduce menstrual pain, one of them was by used the acupressure technique. The purpose of this study was to Determine Whether acupressure was effective in reducing menstrual pain.Methods: The type of research used quasy-experiment. This study used the One Pretest-Posttest Group design. The total samples taken in this study were 31 female students of SMK Negeri 1 Rembang. The Data collected in this study was primary data. The sampling technique used Accidental-Sampling. The statistical test used the Wilcoxon test.Results: The results of this study indicate that there was an effect of acupressure effective in reducing menstrual pain in SMK Negeri 1 Rembang with a value of p value 0,000.Conclusion: From the results of this study it was expected that the female students of make acupressure technique as a way to reduce menstrual pain.